Security cooperation in a strategic competition - Mazarr, Michael J. 1965-; Beauchamp-Mustafaga, Nathan; Blank, Jonah (RAND, 2022)
In this study, RAND researchers examined the current role of security cooperation efforts as a tool in the emerging strategic competition among the United States, Russia, and China. The researchers did not assess the effectiveness or measure outcomes of security cooperation efforts but rather sought to identify how, where, and to what degree the three major competitors-plus Australia, Japan, India, and several countries in Europe-are using security cooperation. To answer this question, the team gathered all available data on the programs of the major countries that lead and usually fund security cooperation activities, examined the national security strategies and official statements of those countries to discover the intent and approach of their security cooperation efforts, and conducted case studies of major junior partners in (or recipients of) security cooperation efforts to see how the competition is playing out on the ground. The researchers found that security cooperation is a growing area of competition; that the United States and its allies enjoy a significant competitive advantage in this space; and that U.S., and particularly U.S. Air Force, security cooperation programs should have a geopolitical and an operational focus. Research for this report was completed in late 2019, and the analysis is supported by the data available at that time
Title from PDF document (title page: viewed April 4, 2022)
"Prepared for the Department of the Air Force
Keywords: Sicherheitspolitik; Internationale Kooperation; Security, International / 21st century; United States / Foreign relations / 21st century